Comparative Anatomy of Five Species from Three Genera of Vitaceae - Külkamp, Josimar; Mattos, Amanda Do Prado (Phytotaxa, 2026)
Vitaceae is a family of considerable economic importance and morphological diversity, in which foliar differences are widely used for generic delimitation, whereas comparative anatomical data of vegetative organs remain scarce for certain structures. In this study, we investigated the stem, petiole, leaf midrib, and tendril anatomy of five species belonging to the genera Nekemias, Parthenocissus, and Vitis collected in the southeastern United States. Our analyses revealed a shared lianescent structural pattern characterized by a continuous vascular cylinder and well-developed secondary growth, together with intergeneric and interspecific variations associated with growth habit and mechanical support. Marked differences were observed in ray organization, vessel diameter, cortex-to-pith proportion, and especially in the distribution and arrangement of phloem fibers. Tendrils exhibited clear cauline affinity, with pronounced secondary growth in Vitis and Nekemias arborea, whereas Parthenocissus quinquefolia displayed more herbaceous characteristics. Our results demonstrate that vegetative organ anatomy provides relevant diagnostic characters and contributes to understanding structural and evolutionary diversification within Vitaceae.